Trailblazer Tepezza for thyroid - Aamna Khatoon; Fatima Kaleem Ahmed; Amna Kaleem Ahmed (Journal of the Pakistan Medical Association)
Dear Editor, Teprotumumab is a human monoclonal antibody that blocks the insulin-like growth factor-1 receptor (IGF- 1R). Approved by the Food and Drug Administration (FDA) on January 21st, 2020, under the brand name Tepezza, to be used as the treatment for Graves eye disease in adults based on its landmark success in the randomised double-blind clinical trials named OPTIC study. [1]